(untitled) (American Journal of Medical Science and Innovation, 2023)
Myiasis is a neglected tropical disease caused by infestation by the larval stages (maggots) of many species of flies, which occur worldwide but are more prevalent in the tropical and subtropical regions. The two main types of flies causing human myiasis are Dermatobia hominis (bot fly) and Cordylobia anthropophaga (tumbu fly). Cases of human myiasis in Kenya are not well documented, but some epidemiological studies show the tumbu fly to be the most prevalent. Transmission and infestation occur in cases of poor personal and environmental hygiene, especially in spaces shared with wild and domestic animals. Cutaneous myiasis, presenting as a furuncular, wound, and migratory disease, is the most common clinical phenotype that may be associated with secondary pyogenic infection and cellulitis, especially when not treated promptly. In this study, we present a case of cutaneous furuncular myiasis in a patient from rural Kenya. We share our experience managing the patient and also provide a literature review on the clinical case management of myiasis, with a call for more epidemiological and clinical work to be done to better understand this neglected disease.